The Influence of Foreign Directors, Capital Expenditures, Financial Constraints, and Profitability on Carbon Emission Disclosure - Triwardoyo, Anggito; Purwanti, Lilik (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2026)
This quantitative study aims to examine the empirical influence of foreign directors, capital expenditure, financial constraints, and profitability on carbon emission disclosure. The energy sector was selected as the research object because it has been the largest contributor to carbon emissions since 2022. Secondary data were obtained from 47 energy sector companies listed on the Indonesia Stock Exchange during the 2021–2024 period and selected using a purposive sampling technique. Data analysis using Stata MP7 indicates that foreign directors and financial constraints do not have a significant effect on carbon emission disclosure, while capital expenditure and profitability have negative effects in opposite directions. These findings are not aligned with stakeholder theory and legitimacy theory, as profitability and capital expenditure tend to prioritize the fulfillment of stakeholders’ interests that are oriented toward non-environmental concerns.